Autophagy and EMT in cancer and metastasis: Who controls whom? - Rohit Gundamaraju; Wenying Lu; Manash K. Paul; Niraj Kumar Jha; Piyush Kumar Gupta; Shreesh Ojha; Indranil Chattopadhyay; Pasupuleti Visweswara Rao; Saeid Ghavami (Elsevier B.V., 2022)
Metastasis consists of hallmark events, including Epithelial-Mesenchymal Transition (EMT), angiogenesis, initiation of inflammatory tumor microenvironment, and malfunctions in apoptosis. Autophagy is known to play a pivotal role in the metastatic process. Autophagy has pulled researchers towards it in recent times because of its dual role in the maintenance of cancer cells. Evidence states that cells undergoing EMT need autophagy in order to survive during migration and dissemination. Additionally, it orchestrates EMT markers in certain cancers. On the other side of the coin, autophagy plays an oncosuppressive role in impeding early metastasis. This review aims to project the interrelationship between autophagy and EMT. Targeting EMT via autophagy as a useful strategy is discussed in this review. Furthermore, for the first time, we have covered the possible reciprocating roles of EMT and autophagy and its consequences in cancer metastasis.